L’intelligence économique dans un contexte d’innovation ouverte : Gestion et protection des connaissances - BAKI, Maha Lamia; TEMR, Leïla; MONTAIGNE, Étienne; DJENANE, Abdel Madjid (Journal of Human Sciences, 2014)
Open innovation, as a new key of success for companies, offers new business opportunities, and most important field of knowledge; but in another hand, this openness creates another form of competition between firms, characterized by a race for the appropriation of knowledge and ideas that allow the anticipation in innovation in a business environment. In such an accentuated competitive context, the challenge is great and the company needs to ensure the production and protection of information and knowledge, and also make sure of their good management in intern or extern (employees, partners, ...) We try to present in this paper the theoretical contribution of business intelligence (BI) and Knowledge Management (KM) in the management and protection of company knowledge in a context of open innovation (OI), and to demonstrate the link and the interaction between the two processes, i.e business intelligence (BI) and Knowledge Management (KM).